LESSONS FROM THE FRONT LINES OF THE 21st CENTURY ECONOMY: The structure of job opportunities in the Massachusetts information technology industry. - Goodman, Michael D. (Career Planning & Adult Development Journal)
This article describes the occupational composition of the Information Technology (IT) industry and the structure of opportunities in this major and growing employment sector. The results of a recent and detailed assessment of the IT industry in Massachusetts are used to identify implications for career development practitioners. The data presented in this article suggest two broad lessons can be learned from the Massachusetts experience: 1) that there are more opportunities for less well educated workers in this sector than is commonly understood, and 2) that the return to the technical skills demanded by growing information technology firms is substantial.